Gambaran Derajat Keasaman (pH) Saliva dan Jumlah Karies pada Mahasiswa di Asrama Intimung Kalimantan Utara - Satya Oktafriana; Taadi Taadi; Almujadi Almujadi (Journal of Oral Health Care, 2017)
Saliva is the liquid in oral cavity that is produced by the three pairs of the big salivary glands, which are parotid saliva, submandibular and sublingual, minor salivary glands, and gingival liquid. The degrees of acidity (pH) in saliva is used to determine the level of acidity (or alkalinity that the liquid has). Caries is one of the side effect of the degree of acidity in saliva that has acids as the criteria. This research was conducted in order to find out the description of the degree of acidity in saliva and the number of caries to the students at Intimung Academy of North Kalimantan in Yogyakarta. The method of this research was descriptive with cross sectional approach. It was conducted on March 2016 and its location was at Intimung Academy of North Kalimantan. The limitation of this research was the degree of acidity in saliva and the number of caries. This research measured the degree of acidity (pH) in saliva and the number of dental caries to the students at Intimung Academy of North Kalimantan with the cross tab management data. The result of the cross tabulation showed that there were 27 students with persentation (48,2 %) of respondents have caries and pH acid in saliva. Conclusions obtained some of the respondents who have a degree of acidity ( pH ) of saliva most is 29 ( 51.8 % ) of respondents . Respondents who have a number of caries bit with 26 ( 46.4 % ) of respondents. Respondents with caries a lot and the degree of acidity ( pH ) neutral saliva is 14 ( 25 % ) of respondents.